2014
DOI: 10.3389/fnhum.2014.00327
|View full text |Cite
|
Sign up to set email alerts
|

Investigating bottom-up auditory attention

Abstract: Bottom-up attention is a sensory-driven selection mechanism that directs perception toward a subset of the stimulus that is considered salient, or attention-grabbing. Most studies of bottom-up auditory attention have adapted frameworks similar to visual attention models whereby local or global “contrast” is a central concept in defining salient elements in a scene. In the current study, we take a more fundamental approach to modeling auditory attention; providing the first examination of the space of auditory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
89
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 67 publications
8
89
0
Order By: Relevance
“…In particular, the other features seem helpful in establishing salient events in the context of acoustically dense scenes, in which the difference in loudness between the background and the salient sound is much lower. This finding is supported by Kaya et al 39 which showed that the contribution to salience from different features varied across sound classes. The Kaya et al study used comparatively more dense acoustic stimuli.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In particular, the other features seem helpful in establishing salient events in the context of acoustically dense scenes, in which the difference in loudness between the background and the salient sound is much lower. This finding is supported by Kaya et al 39 which showed that the contribution to salience from different features varied across sound classes. The Kaya et al study used comparatively more dense acoustic stimuli.…”
Section: Discussionsupporting
confidence: 68%
“…The second is a model by Kim et al, 19 which calculates salient periods using a linear salience filter and linear discriminant analysis on loudness. The third is a model by Kaya et al, 18 which detects deviants in acoustic features using a predictive tracking model using a Kalman filter. While the first two models are implemented as published in their original papers, the Kaya model is used with features expanded to include all the features included in the current study.…”
Section: F Event Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…The former is a measure of the novelty of a sound "event", whereas the latter represents the quality driving the formation of the auditory foreground and background. We will focus on perceptual salience, complementing the literature on salience models that exclusively addresses sensory salience [5][6][7][8][9][10][11]. We equate perceptual salience with faster and more accurate stream selection.…”
Section: Introductionmentioning
confidence: 99%